Pollen morphology of some Nepeta L. Taxa in Uzbekistan - Makhkamov, Trobjon; Rahmatov, Abdurashid; Zafar, Muhammad; Elshikh, Mohamed S.; Al Farraj, Dunia A.; Yuldashev, Akramjon; Islamov, Sokhib; Sotiboldiyeva, Dilnoza; Makkamov, Zokirjon; Khakimova, Dilabza; Allaberdiev, Rustamjon; Ptaszyńska, Aneta A.; et al. (Genetic resources and crop evolution, 2025)
The taxonomic classification of the Nepeta genus (Lamiaceae) and its intrageneric species has long been a subject of debate. This study aims to comprehensively examine the palynological characteristics of selected Nepeta species and compare these findings with their phylogenetic relationships and taxonomic classifications. Using scanning electron microscopy, the pollen morphology of 10 species within Nepeta genus was meticulously investigated. Measurements, observations, and statistical analyses were conducted on eight quantitative features and five qualitative ones of the pollen grains. The study showed several key characteristics of Nepeta pollen. These included their monad, hexacolpate, hexacolporate, and Stephanocolpate nature, ranging a size range from small to large (14.39–58.42 μm) and exhibiting elongated prolate to oblate shapes. Furthermore, the examination of exine ornamentation under SEM revealed three distinct sexine sculpture types: type I-reticulate with micro-perforations, type II-micro-reticulate with macro-perforations, and type III-bi-reticulate. The principal component analysis (PCA) was validating the distinct separation of Nepeta species based on quantitative pollen grain variables. Concerning exine patterns and aperture numbers, the Nepeta genus stands out from other Lamiaceae genera due to its pollen being 6-colporate with a bi-reticulate perforated exine. The findings developed the taxonomic dichotomous key based on Nepeta species pollen signify the qualitative traits explained the micromorphology of palyno-morphs identification of Nepeta genus as Stenopalynous. However, this study holds implications for Lamiaceous species comparative morphological, taxonomic, and phylogenetic interpretations.